De Motu Animalium and Practical Syllogism Revisited - Casanova, Carlos Augusto (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This paper contains a general exposition of De Motu Animalium, particularly chapters 6 to 11. The goal is to prove that this Aristotelian work cannot be used to ground the opinion that practical syllogism concludes in action and not in judgment. The contrary thesis, held by several authors like Elizabeth Anscombe, Martha Nussbaum, and Alejandro Vigo, is refuted. What the«explanation of an elective action» consists in is a particular consideration.